Cathelicidins in inflammation and tissue repair: Potential therapeutic applications for gastrointestinal disorders - Kei Wu William Ka; Man Wong Clover Ching; Li Zhi Jie; Zhang Lin; Ren Shun Xiang; Cho Chi Hin (Acta Pharmacologica Sinica, 2016)
Cathelicidins, a family of host defense peptides, are highly expressed during infection, inflammation and wound healing. These peptides not only have broad-spectrum antimicrobial activities, but also modulate inflammation by altering cytokine response and chemoattraction of inflammatory cells in diseased tissues. In this connection, a mouse cathelicidin has been demonstrated to prevent inflammation in the colon through enhancing mucus production and reducing production of pro-inflammatory cytokines. In addition, cathelicidins promote wound healing through stimulation of re-epithelialization and angiogenesis at injured tissues. In an animal model of gastric ulceration, the rat cathelicidin promotes ulcer healing by inducing proliferation of gastric epithelial cells both in vitro and in vivo. In conclusion, cathelicidins represent an important group of effector molecules in the innate immune system that operates a complex integration of inflammation and tissue repair in the gastrointestinal mucosa and other organs.